2017
DOI: 10.1002/mrc.4686
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency ESR studies on permeable and impermeable deuterated nitroxyl radicals in corn oil solution

Abstract: Low-frequency electron spin resonance studies were performed for 2 mM concentration of deuterated permeable and impermeable nitroxyl spin probes, 3-methoxycarbonyl-2,2,5,5-tetramethyl-pyrrolidine-1-oxyl and 3-carboxy-2,2,5,5,-tetramethyl-1-pyrrolidinyloxy in pure water and various concentrations of corn oil solution. The electron spin resonance parameters such as the line width, hyperfine coupling constant, g factor, rotational correlation time, permeability, and partition parameter were estimated. The broaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It means that PCA in the viable skin layer was of high mobility and in a hydrophilic microenvironment (Table 2 ). PCA is generally considered as a cell membrane-impermeable probe due to its hydrophilicity [ 40 ]. However, several studies showed that PCA could enter cells, even though the intracellular amount was much lower than the intercellular one [ 48 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that PCA in the viable skin layer was of high mobility and in a hydrophilic microenvironment (Table 2 ). PCA is generally considered as a cell membrane-impermeable probe due to its hydrophilicity [ 40 ]. However, several studies showed that PCA could enter cells, even though the intracellular amount was much lower than the intercellular one [ 48 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is different from many published findings, which stated that the PBS-ethanol cosolvent was better than the pure solvents, e.g., ethanol or PBS [ 26 – 29 ]. PCA is a small hydrophilic molecule (186 g/mol) with a natural logarithmic partition coefficient of −1.8 [ 40 ]. With the hydration of the SC by PBS [ 41 , 42 ], possibly the solubility of PCA in the SC was increased, and hence the penetration of PCA into the SC could be enhanced.…”
Section: Resultsmentioning
confidence: 99%